Factors influencing work related stress among employees in Etiqa insurance & Takaful berhad - Ab.Aziz, Irlina Emiera; Tuan Mohamad, Sharifah Ummu Atifah (2013)
Nowadays, Stress becomes a major problem to the employees and worst to them as it could affect their job performance as well as other problem related to their life and career. Stress can bring bad performance to the employees and organization. Etiqa Insurance & Takaful Berhad is one of the companies which most of their employees will socialize with the people in order to attract them to deal and purchasing their Insurance and Takaful product. Most of their employee will face with stress in their working day as they need to entertain their customer and clients in getting their business. The main purpose of this study is to recognize the main factor which most influencing the stress among them. The respondent from this study are 51 employees from different job categories such as managers, clerk, executive, and agents that work in Etiqa Insurance and Takaful Berhad. The researcher had used convenience sampling as a sampling technique. The process of analyzing and interpreting data has been presented by figures and tables using method of reliability test, frequency, descriptive statistic and correlation. The researcher also provided some recommendations to help the future researcher in improving their research regarding to this topic.